Effect of Alpha Lipoic Acid Supplementation on Oxidative Stress and Lipid Parameters in Women Diagnosed with Low-Grade Squamous Intraepithelial Lesions (LSILs): A Double-Blind, Randomized, Placebo-Controlled Trial - Anja Divković; Zinaida Karasalihović; Ivana Rumora Samarin; Damir Sabitović; Kristina Radić; Nikolina Golub; Lovorka Vujić; Marija Grdić Rajković; Dubravka Vitali Čepo (MDPI AG, 2023)
Limited scientific evidence shows that alpha lipoic acid (ALA) can induce regression rates of low-grade squamous intraepithelial lesions (LSILs), but the mechanisms of these effects have not been elucidated. To gain a broader insight into its therapeutic potential and mechanisms of action, the effects of 3 months of supplementation with 600 mg of ALA on antioxidant and lipid status parameters in 100 patients with LSILs were investigated in a randomized, placebo-controlled study. The obtained results are discussed in terms of patients' initial metabolic status and diet quality (particularly nutritional intake of antioxidants). The obtained results showed that oxidative status biomarkers were not significantly affected by ALA supplementation. However, serum superoxide dismutase (SOD) activity was positively affected in the subgroup of patients with higher dietary antioxidant intake. Surprisingly, ALA supplementation resulted in a small but statistically significant increase in serum low density lipoprotein (LDL), and the observed effect was significantly affected by the initial lipid status of the participants. Larger studies are necessary to gain additional insights on the clinical significance of ALA as an antioxidant and hypolipemic agent and to optimize its potential application in LSIL treatment.